Heterogeneous Trade Elasticity and Managerial Skills - Maria Bas; Lionel Fontagné; Irene Iodice; Gianluca Orefice (CESifo GmbH, 2025)
This paper investigates the role played by firms' managerial skills in the heterogeneous reaction of exporters to common exogenous changes in their international competitiveness (here captured by changes in the real exchange rate). Relying on a simple theoretical framework, we show that firms with better managerial skills have higher profits, market power, and are able to adapt their markup more when faced with a competitiveness shock. We test this prediction relying on detailed firm-product-destination level export data from France for the period 1995-2007 matched with specific information on the firms' share of managers. Our findings show that managerial intensive firms have larger exporter price elasticity to real exchange rate variations. The effect is not trivial: in the wake of a depreciation, exporters whose management intensity is one standard deviation higher than the average, increase their prices by 51% to 73% more than the average exporter. This finding is robust to controlling for the alternative explanations suggested by the previous literature to explain the heterogeneous pass-through of firms.
Keywords: F12; F14; F31; 330; exchange rate pass-through; heterogeneous pricing-to-market; managerial skills